Analisa Faktor Penerimaan Sistem E-Learning Narotama Menggunakan Metode Technology Acceptance Model - Addin Cendekia Wahid (Syntax Corporation Indonesia, 2024)
E-learning is a learning method using information technology, which is designed so that each individual can learn independently. E-learning provides flexibility in choosing the time and place to access subject matter, as well as providing opportunities for learners to take control of their learning success. At Narotama University in Surabaya, the E-learning system used is the result of independent development by the university, which is named the Elina system (Narotama E-learning). The elina system is used by the academic community, lecturers and students who have a background in technological insight, infrastructure, and various main tasks. This diversity can affect behavior / perceptions of system use. Technology Acceptance Model (TAM) is a theory about the use of information technology systems which is considered very influential and is generally used to explain individual acceptance of the use of information technology systems. This study aims to analyze the factors that affect the acceptance of Elina's system by lecturers at Narotama University Surabaya using the Technology Acceptance Model (TAM) method. The TAM that will be used comes from previous research, namely Perceived Usefulness, Perceived Ease of Use, Intention To Use, and Actual Technology Use. With the addition of Learning Interface Design and Accessibility System in Multiplatform constructions. The results showed that the factors of Learning Interface Design and Accessibility System in Multiplatform had an indirect effect on Elina's Actual Technology Use system by Narotama University lecturers through the factors of Perceived of Usefulness, Perceived Ease of Use and Intention to Use.